"This Is What I Should Have Been Feeling": Transformations and Transitions in an LGBTQIA+ Inclusive Rugby Club - Eldridge, David (International Journal of Educational and Life Transitions, 2025)
Across the UK, LGBTQIA+ sports clubs have become an established feature of the grassroots sporting landscape, with networks such as International Gay Rugby (IGR) expanding rapidly over the past two decades.  Their continued growth suggests that many LGBTQIA+ people still perceive mainstream sport as exclusionary or unwelcoming.  Yet scholarship remains limited, and studies grounded in Inclusive Masculinity Theory (IMT) frequently posit that declining homophobia has rendered such clubs primarily social spaces rather than sites of necessary protection or transformation.This article applies Multiple and Multidimensional Transitions (MMT) theory to the experiences of 14 gay and bisexual rugby players, to examine the ongoing relevance and value of LGBTQIA+ inclusive sports spaces.  It shows how joining an inclusive rugby team prompts a dynamic set of interconnected transitions across psychological, cultural, identity and social domains.  By highlighting these ongoing multidimensional processes, MMT demonstrates that LGBTQIA+ sports teams remain vital not merely as alternatives to homophobic environments, but as spaces that actively construct queer belonging and enable more expansive, authentic ways of being in sport.
Keywords: LGBTQIA+; homophobia; inclusive sports; International Gay Rugby (IGR); physical education; Multiple and Multidimensional Transitions; Inclusive Masculinity Theory; Inclusive Masculinity Theory